PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PADA MATERI HIDROKARBON DALAM MENINGKATKAN HASIL BELAJAR KOGNITIF PESERTA DIDIK - Sugito Sugito; Uli Maharani Suyadi (Universitas Papua, Manokwari, Indonesia, 2021)
Abstract Education is a process of changing attitudes and behavior of a person or group in an effort to mature humans through teaching and training efforts; process, method, act of educating. This study aims to improve student learning outcomes through the application of the Problem Based Learning learning model on the Hydrocarbon class XI MIA 3 SMA Negeri 1 Prafi and to see the magnitude of the increase in student learning outcomes on the Hydrocarbon subject matter. This research uses Classroom Action Research (CAR) with Kurt Lewin's CAR model. The increase in student learning outcomes can be seen from the results of the pre-test and post-test that have been given to students. The data obtained were then analyzed using descriptive analysis techniques with the help of Microsoft Excel 2013 to describe the increase in each cycle. The application of the Problem Based Learning learning model, cognitive learning outcomes have increased from cycle 1 with an average value of 68.18 with the number of students achieving a KKM score of 45% and in cycle 2 with an average value of 79.40 with the number of students who achieve the KKM value of 82% so that there is an increase in the percent increase in classical learning outcomes of students 37% Keywords: Learning Model’s, Problem Based Learning, learning outcomes, Classroom Action Research